Perangkap Cahaya Sebagai Komponen Pengendalian Hama Terpadu Di Kelompok Wanita Tani Mawar Bodas Kota Tasikmalaya - R. Arif Malik Ramadhan; Selvy Isnaeni (Jurnal Pengabdian Pada Masyarakat, 2022)
The most common pest control carried out in the city of Tasikmalaya is by using synthetic pesticides. The concept of integrated pest control (IPM) in the community aims to suppress the use of synthetic pesticides. Application of IPM can be implemented by integrating various types of compatible controls based on economic, ecological, and social considerations. The use of light traps is one of IPM components that easy to implement to monitor the presence of insects in an agroecosystem. The use of this light-trapping technology received a positive response from partner communities, agricultural extension workers, and local governments. Based on the data collected during the implementation of this program, it is known that there is an increase in knowledge and skills and the use of light trapping technology in the partner community. There is an increase in knowledge related to terms and the use of light traps by 100%, an increase in knowledge about the time of applying light traps by 37.5%, an increase in respondents skills in assembling simple light traps by 100%, and the application of light trapping technology by partner communities by 88.9 %.